2021
DOI: 10.1021/acs.chemrestox.0c00406
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biochemical Insights into the Inhibition of Human Acetylcholinesterase by G-Series Nerve Agents and Subsequent Reactivation by HI-6

Abstract: The recent use of organophosphate nerve agents in Syria, Malaysia, Russia, and the United Kingdom has reinforced the potential threat of their intentional release. These agents act through their ability to inhibit human acetylcholinesterase (hAChE; E.C. 3.1.1.7), an enzyme vital for survival. The toxicity of hAChE inhibition via G-series nerve agents has been demonstrated to vary widely depending on the G-agent used. To gain insight into this issue, the structures of hAChE inhibited by tabun, sarin, cyclosarin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 33 publications
(79 reference statements)
1
11
0
Order By: Relevance
“…This stabilization then pulls the whole substituted phosphorus towards W86. A similar shift is observed in the structure the just-slightly-smaller Soman-hAChE conjugate [20].…”
Section: Effects Of Conjugation Of the Novel A-type Nerve Agent Ops To Hachesupporting
confidence: 76%
“…This stabilization then pulls the whole substituted phosphorus towards W86. A similar shift is observed in the structure the just-slightly-smaller Soman-hAChE conjugate [20].…”
Section: Effects Of Conjugation Of the Novel A-type Nerve Agent Ops To Hachesupporting
confidence: 76%
“…h AChE and m AChE are very similar in sequence and 3D structure, and studies have shown similar inhibition kinetics [66,67] . Also, binary OPNA‐AChE complex structures determined in both species are similar [12,13,15,16] . The molecular structure confirmed that the aromatic scaffold of 1 a interacts with amino acid residues at the entrance of the gorge, with the amine substituent extending towards the catalytic site (Figures 2B and S3).…”
Section: Resultsmentioning
confidence: 56%
“…The electron density maps show that binding modes A and B of the aromatic scaffold position the pyridinium oxime in close proximity to the serine phosphoesters of tabun and RVX (mode A) and VX (mode B) whereas in mode C the oxime is far from the catalytic site inhibited by sarin. The promiscuity of the peripheral site of OPNA‐ h AChE in accommodating aromatic scaffolds has also been observed for HI‐6 [12,13] . In this case different arene‐arene interactions lead to different binding poses for the aromatic scaffold of HI‐6, while the linker and pyridinium oxime are directed towards the active site for all HI‐6 ⋅ OPNA‐ h AChE species.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations